Gut microbial profile of treatment-naive patients with primary biliary cholangitis - Zhou, Yi-jun; Ying, Gao-xiang; Dong, Shi-lei; Xiang, Bo; Jin, Qiao-fei (Frontiers in Immunology, 2023)
Background and aims The pathogenesis of primary biliary cholangitis (PBC) is associated with alterations of gut microbiota. We compared the gut microbiota of PBC patients and healthy controls from Zhejiang Province and assessed the use of these data for the diagnosis of PBC. Methods First, 16S rRNA gene sequencing was used to characterize the gut microbiota of treatment-naive PBC patients (n=25) and matched healthy controls (n=25). Then, the value of gut microbiota composition for the diagnosis of PBC and assessment of PBC severity was determined. Results The gut microbiota of PBC patients had lower diversity based on three different metrics of alpha-diversity (ace, Chao1, and observed features) and fewer overall genera (all p<0.01). PBC patients had significant enrichment of four genera and significant depletion of eight genera. We identified six amplicon sequence variants (Serratia, Oscillospirales, Ruminococcaceae, Faecalibacterium, Sutterellaceae, and Coprococcus) as optimal biomarkers to distinguish PBC patients from controls based on receiver operating characteristic analysis (area under the curve [AUC] = 0.824). PBC patients who were anti-gp210-positive had lower levels of Oscillospiraceae than those who were anti-gp210-negative. KEGG functional annotation suggested the major changes in the gut microbiota of PBC patients were related to lipid metabolism and biosynthesis of secondary metabolites. Conclusion We characterized the gut microbiota of treatment-naive PBC patients and healthy controls from Zhejiang Province. The PBC patients had significant alterations in their gut microbiota, suggesting that gut microbiota composition could be useful as a non-invasive tool for the diagnosis of PBC.